Resting Muscle Shear Modulus Measured With Ultrasound Shear-Wave Elastography as an Alternative Tool to Assess Muscle Fatigue in Humans - Siracusa, Julien; Charlot, Keyne; Malgoyre, Alexandra; Conort, Sébastien; Tardo-Dino, Pierre-Emmanuel; Bourrilhon, Cyprien; Garcia-Vicencio, Sebastian (Frontiers in Physiology, 2019)
The aim of this study was to investigate the time course of the resting vastus lateralis (VL) muscle shear elastic modulus (µ) measured with ultrasound shear-wave elastography during repetition of isometric maximal voluntary contractions (MVCs) of the knee extensors (KE). Fifteen well-trained males repeated 60 5-s isometric MVCs. Evoked electrical stimulations and the VLµ were measured every ten MVCs at rest. The resting VLµ significantly decreased (-34.7 ± 6.7%; P < 0.001) by the end of the fatigue protocol. There was also a 38.4 ± 12.6 % decrease in MVC after exercise (P < 0.001). The potentiated doublet and single twitch torque amplitudes and properties were significantly modified by the end of exercise (P < 0.001). This study shows the time course of the resting VLµ during the repetition of maximal voluntary fatiguing exercise of the KE muscles. The decrease of the resting VLµ could directly affect the force transmission capabilities accounting for peripheral fatigue.